Malondialdehyde, Glutathione, and Nitric Oxide Levels in Toxoplasma gondii Seropositive Patients - Karaman, Ulku; Celik, Tuncay; Kiran, Tugba Raika; Colak, Cemil; Daldal, Nilgun Ulfet (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2008)
The aim of this study was to investigate the difference in the serum malondialdehyde (MDA), glutathione (GSH), and nitric oxide (NO) levels between normal and T. gondii-infected patients. To this end, MDA, GSH, and NO levels in the sera of 37 seropositive patients and 40 participants in the control group were evaluated. In Toxoplasma ELISA, IgG results of the patient group were 1,013.0 +/- 543.8 in optical density (mean +/- SD). A statistically significant difference was found between patients and the control group in terms of MDA, GSH, and NO levels. A decrease in GSH activity was detected, while MDA and NO levels increased significantly. Consequently, it is suggested that the use of antioxidant vitamins in addition to a parasite treatment shall prove useful. The high infection vs control ratio of MDA and NO levels probably suggests the occurrence as a mechanism of tissue damage in cases of chronic toxoplasmosis. Moreover, it is recommended that the patient levels of MDA, GSH, and NO should be evaluated in toxoplasmosis.
Keywords: Toxoplasma gondii; malondialdehyde; glutathione; nitric oxide